Enhancer RNA - P2RY2e induced by estrogen promotes malignant behaviors of bladder cancer - Ding, Mengting (Int J Biol Sci, 2018)
Enhancers are transcriptional regulatory elements that increase target gene expression. It has reported that enhancers could universally transcribe into enhancer RNAs (eRNAs) with stimulation. Increasing evidence showed eRNAs participated in various disease processes including malignant tumors. P2RY2 enhancer RNA (P2RY2e) is an estrogen-responsive eRNA and involved in the development of breast cancer. However, the relationship between P2RY2e and bladder cancer (BCa) is unclear. In the study, we discovered that P2RY2e was upregulated in BCa tissues and estrogen-treated cells. Estrogen promoted the malignant abilities of BCa cells. P2RY2e knockdown by CRISPR-Cas13a inhibit the cell multiplication, invasion and migration. Additionally, the cell apoptosis was facilitated. What's more, downregulation of P2RY2e could weaken the cancer-promoting effects of estrogen on BCa. Our study revealed that P2RY2e played a carcinogenic role in BCa and estrogen might promote the initiation of BCa by inducing P2RY2e. We provide a potential therapeutic target for BCa and a new perspective for the tumorigenesis of bladder cancer.